Relaxation Method Training to Reduce Stress Levels in Mothers - Eva Gustiana; Nika Cahyati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The purpose of implementing community service is in the form of training on relaxation methods to reduce stress levels for mothers during online learning, this training is to increase the ability to reduce stress on parents, especially mothers to accompany children during online learning. This training was carried out for parents of RA students in Darma District, Kuningan Regency, the issue was about the number of parents who were stressed because they accompanied their children in learning during online learning. In fact, as it is known that the current changes in the situation and conditions of Covid that affect the condition of parents so that not a few are experiencing stress, with the existing phenomena in the field, therefore, this service aims to reduce stress levels for mothers in accompanying children, during School From Home. This service activity is in the form of training and guidance consisting of several stages, namely the observation stage, the collaboration stage with PC IGRA Darma, the guidance preparation stage, the training stage and the evaluation stage. Based on the results of data analysis shows that the relaxation method can reduce stress levels in mothers when accompanying School From Home children.